Physical and Chemical Characteristic of Snack Bars from Jewawut Flour and Mocaf as Effect of Temperature and Roasting Time: Karakteristik Fisik dan Kimia Snack Bar dari Tepung Jewawut dan Mocaf Sebagai Efek Suhu dan Lama Pemanggangan - Jamilah, Nurul; Hidayati, Darimiyya; Purwandari, Umi (Universitas Slamet Riyadi Surakarta, 2024)
Snack bars are processed food products that shaped rectangular or like a bar. Snack bar in this study used ingredients of barley flour and mocaf. Barley is a potential ingredient as a source of dietary fiber and gluten-free mocaf can fix the texture of barley. One of the factors that affects the quality of the snack bar is the baking process. The purpose of this study was to determine the effect of temperature and baking time on the characteristics of physical, chemical, and sensory of the snack bar, and to determine best formulation of the temperature and baking time of the snack bar. The design applied was a completely randomized design with two factors consisting baking temperature of 130 and 160°C, and baking time of 20 minutes and 40 minutes. The results showed that baking time had a significant effect on the values of a and b, but not significant on the value of L. Baking temperature and time had a significant effect on the level of preference for texture, color, overall and on texture and color on sensory quality. However, it had no significant effect on aroma and taste. The baking temperature had a significant effect on the moisture content, but roasting time had no significant effect. The best snack bar was that baked at 160ºC, 20 minutes. The best formulation of snack bar contains nutrients, water content of 15%, ash of 1.906%, fat 19.447%, protein 21.012%, carbohydrates 42.635%, dietary fiber 11.262% and total calories 429 kcal.